2015
DOI: 10.4103/0973-1482.165878
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy in advanced sinonasal teratocarcinosarcoma with intracranial extension: Report of two cases with literature review

Abstract: Sinonasal teratocarcinosarcoma (SNTCS) is a highly aggressive rare tumor of the nasal cavity. Surgery followed by concurrent chemoradiation is the mainstay of treatment in SNTCS. However, intracranial extension may complicate surgical resection, with difficulty in achieving R0 resection. Here we present two cases of SNTCS with intracranial extension; both patients were seen in skull base clinic of our hospital and deemed unsuitable for surgery. These patients then were offered neoadjuvant chemotherapy (NACT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Sinonasal teratocarcinosarcoma can rapidly spread intracranially and has a high rate of recurrence . In almost half of reported cases, the patients died within 3 years of tumor diagnosis, despite aggressive therapy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinonasal teratocarcinosarcoma can rapidly spread intracranially and has a high rate of recurrence . In almost half of reported cases, the patients died within 3 years of tumor diagnosis, despite aggressive therapy .…”
Section: Discussionmentioning
confidence: 99%
“…In their 2 cases, Joshi et al used neoadjuvant chemotherapy. Neoadjuvant therapy is being explored as an option for large and unresectable SNTCS in the hope that improved surgical outcomes and reduced morbidity and mortality may be possible in these cases; however, more data are required to assess its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…1322,2629 Recently, neoadjuvant chemotherapy prior to operation has been suggested. 31 The local recurrence rate ranges from 25% to 55%. 5,2729,32,33 Thus, follow-up nasal endoscopy and/or positron-emission tomography-CT is essential to screen for early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature revealed 11 cases of TCS with intracranial invasion [ Table 1 ]. [ 3 6 7 8 9 16 17 19 20 21 ] Although the documented cases with predominant intracranial involvement are scarce, treatment with surgical resection with or without adjuvant treatments of chemotherapy and radiation therapy is the most widely accepted with goal for gross total resection. Despite few intracranial cases described in the literature, patients undergoing gross total resection fare better than those with subtotal resection.…”
Section: Discussionmentioning
confidence: 99%